PENGARUH IMPLEMENTASI KURIKULUM MERDEKA TERHADAP KINERJA GURU PADA SEKOLAH PENGGERAK JENJANG PENDIDIKAN ANAK USIA DINI (PAUD) DI KABUPATEN MAJENE - Asdar Asdar; Nur Hafsah Yunus; Herlina Ahmad; Arifin Tahir; Kurnia Kurnia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
This research was conducted at the PAUD level driving school in Majene Regency, West Sulawesi Province. The subjects in this study were 24 teachers from 4 PAUD schools throughout Majene Regency. questionnaire techniques, observation and documentation. Based on the results of the analysis of 23 teachers from 4 second-generation driving schools in Majene Regency, namely Usman Bin Affan Kindergarten/PAUD with 12 teachers, Asyiyah Barane Kindergarten with 1 teacher, Salabose Kindergarten with 6 teachers, and Muttiamah Kindergarten with 4 teachers, it can be seen that the mean of the implementation of the independent curriculum is 87.75 or is in the interval 75-90 which means that the implementation of the independent curriculum in kindergartens/PAUD driving schools throughout Majene Regency, Batch-2 is included in the